ANALISIS EFEKTIVITAS PELAKSANAAN PROGRAM ADIWIYATA DI SMA NEGERI 4 PONTIANAK - Riani Fitri, Eliza (Universitas Tanjungpura, 2018)
The aim of this research was to know about application of parenting by single parents (mother) in terms of achievement of formal education. The techniques of data collection were observation, interview and the study of documentation, where as the tools of data collection were the directive of observation, directive of interview, the notes and the files like report, trophy, and certificate. This research sources were primer data and secodary data. The result of this research proves that single parents (mother) apply different parenting patterns. Usually, job is single parents